Functional safety and survivability of information control elliptic-curve-based systems: models and methods - ALEKSANDER, Marek A.; KARPINSKI, Mikolaj P.; LITAWA, Grzegorz K. (Ukrainian Scientific Journal of Information Security, 2013)
There is an analysis of functional safety and survivability of information control systems relying on elliptic curve-based calculations. Time required for solving a discrete logarithm on GF(p) elliptic curves was worked out. Presented were aspects of the use of FPGA systems whose calculations were based on Rademacher-Krestenson’s remaining classes and parallel summing.